Pengembangan Media Pembelajaran Interaktif Berbantu Aplikasi Pear Deck dalam Pembelajaran Menyimak di Sekolah Dasar - Hastuti, Nia; Kurniaman, Otang; Mulyani, Eva Astuti (CV. Rayyan Dwi Bharata, 2025)
This research aims to develop a product in the form of interactive learning media for listening learning in elementary schools that is valid and practical. The method used in this research is the Research and Development development method using the ADDIE model. The ADDIE model has 5 stages starting with Analysis, Design, Development, Implementation and Evaluation. In developing this interactive media, researchers validated it with 3 validators consisting of media experts and material experts. To see the practicality of the media being developed, researchers conducted limited trials. The data collection techniques used in this research were interviews, observation and questionnaires. The analysis technique used by researchers is qualitative descriptive analysis and quantitative analysis. Based on the results of the validity test, it shows that the interactive learning media developed received a very valid category with a score of 89.33. Meanwhile, the practicality of interactive learning media based on the teacher response questionnaire obtained a score of 91.67 with very valid criteria and based on the practicality questionnaire, student responses obtained a score of 94.03% with very valid criteria. The listening test in the form of objective questions regarding the short story